Metode Komunikasi Guru Kelas XI Dalam Mengoptimalkan Minat Belajar Siswa SMA Negeri 12 Sinjai - suriyati, Suriyati; Jamaluddin, Jamaluddin; Nurfadillah, Nurfadillah (LP2M Universitas Islam Ahmad Dahlan, 2023)
The purpose of this writing is to describe the communication methods used by class XI teachers to optimize students' interest in learning at SMA Negeri 12 Sinjai. This research is naturalistic research. The subjects of this research were teachers and students of SMA Negeri 12 Sinjai. The subject of this research is the communication method of class XI teachers to optimize students' learning interest. Data collection techniques in this research are interviews and observation. Data analysis techniques use data collection, data reduction, data presentation and data verification. Based on the research results, it was concluded that the methods used by teachers in communicating in class were informative, educational and channelization methods. Meanwhile, psychologically, the existence of supporting facilities and infrastructure, as well as student awareness are supporting factors in optimizing teacher interest in communication methods in the classroom. On the other hand, there are factors that hinder teachers in increasing students' interest in learning, low self-awareness of students, environmental factors and limited time to deliver material in the teaching and learning process in the classroom.